An in vitro model to evaluate the impact of environmental fine particles (PM0.3-2.5) on skin damage. (1st May 2019) - Verdin, Anthony; Cazier, Fabrice; Fitoussi, Richard; Blanchet, Natacha; Vié, Katell; Courcot, Dominique; Momas, Isabelle; Seta, Nathalie; Achard, Sophie
Highlights: Airborne particles induce skin damage. Oxidative and inflammatory pathways modulation after skin exposure to PM. Premature skin ageing after PM exposure. Abstract: Exposure to airborne particulate matter (PM) has significant effects on human health mainly leading to cardio-respiratory diseases. However very few data are available regarding the impact of PM on the skin, so to better understand the impact of fine particle (PM0.3-2.5 ) on both inflammatory response and epidermal structure, we exposed a reconstructed human epidermis (RHE) to several doses of PM collected in Cotonou (Benin, West Africa). After 24 h of exposure, inflammatory response, histological observations, and gene expression related to oxidative stress, antioxidant defense and structural damages were determined. No PM-linked changes in tissue morphology or membrane integrity were observable. PM was however cytotoxic in a dose dependent manner. An inflammatory response appeared as shown by the increase in IL-1α and IL-8 cytokine productions. PM also induced oxidative stress, leading to an increase in 4-HNE immunostaining and to the up-regulation of HMOX1, MT1G and MT1E . Finally, PM had a negative impact on fundamental skin functions such as tissue anchorage, cell differentiation, cornification / skin desquamation and apoptosis. Our data show that airborne fine particles have an adverse effect on skin integrity, most probably leading to accelerated ageing.